2013
DOI: 10.1107/s0108270113006720
|View full text |Cite
|
Sign up to set email alerts
|

Semi-maleate salts ofL- andDL-serinium: the first example of chiral and racemic serinium salts with the same composition and stoichiometry

Abstract: L-serinium semi-maleate, (I), and DL-serinium semi-maleate, (II), both C3H8NO3(+)·C4H3O4(-), provide the first example of chiral and racemic anhydrous serine salts with the same organic anion. A comparison of their crystal structures with each other, with the structures of the pure components (L-serine polymorphs, DL-serine and maleic acid) and with other amino acid maleates is important for understanding the formation of the crystal structures, their response to variations in temperature and pressure, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As observed for FA:Gly 2 , the main structural features of MA:Gly are also present in known binary crystals of MA with other amino acids namely, alanine (MA:Ala), ,, valine (MA:Val , and MA:Val 2 ), leucine (MA:Leu), methionine (MA:Met), phenylalanine, (MA:Phe), ,,, serine (MA:Ser), threonine (MA:Thr), lysine (MA:Lys), and histidine (MA:His, and MA 2 :His) . Regardless of the stoichiometry: (i) they are all salts.…”
Section: Results and Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As observed for FA:Gly 2 , the main structural features of MA:Gly are also present in known binary crystals of MA with other amino acids namely, alanine (MA:Ala), ,, valine (MA:Val , and MA:Val 2 ), leucine (MA:Leu), methionine (MA:Met), phenylalanine, (MA:Phe), ,,, serine (MA:Ser), threonine (MA:Thr), lysine (MA:Lys), and histidine (MA:His, and MA 2 :His) . Regardless of the stoichiometry: (i) they are all salts.…”
Section: Results and Discussionmentioning
confidence: 67%
“…The preference of FA to form cocrystals and of MA to form salts with amino acids seems to be of general scope since it has been observed in all published cases mentioned above. [23][24][25][26]28,[30][31][32][33][34][35][36][37][38][39]43,59,61,62 This tendency cannot be unequivocally predicted from commonly used ΔpK a rules, 40−42 albeit a larger proton transfer ability of MA compared to FA might be anticipated given that pK a1 (MA) < pK a1 (FA). Thus, in the case of the FA + Gly and MA + Gly systems studied here, based on pK a1 (Gly) = 2.35, pK a1 (FA) = 3.02, and pK a1 (MA) = 1.92, at 298 K, 63 it can be concluded that ΔpK a (FA) = −0.67 and ΔpK a (MA) = 0.43.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resonance-assisted hydrogen bond (RAHB) locks the ring in a rigid, planar cis conformation, with an estimated stabilization of 21.5(2) kcal/mol . The properties of this particular hydrogen bond have been the subject of extensive research, including X-ray and neutron diffraction and NMR, vibrational, , and photoelectron spectroscopies, as well as theoretical investigations. ,− This relatively simple system is used as a prototype for the hydrogen transfer processes in enzymatic reactions and DNA intercalations by ortho -hydroxyaryl Schiff bases. , However, the features of this RAHB depend on the environment, including the effect of solvation by polar solvents. …”
Section: Introductionmentioning
confidence: 99%
“…(L-SerH).H 2 PO 4 [11], di-L-serinium hexafluorosilicate (L-SerH) 2 SiF 6 [12], L-serinium hydrogen oxalate (L-SerH)HC 2 O 4 , two forms of di-L-serinium oxalate dihydrate (LSerH) 2 C 2 O 4 .2H 2 O [13,14], L-serinium hydrogen maleate [15].…”
Section: Introductionmentioning
confidence: 99%